RETRACTED: The Role of microRNAs in the Tumorigenesis of Ovarian Cancer - Di Leva, Gianpiero; Croce, Carlo M. (Frontiers in Oncology, 2013)
Epithelial ovarian cancer (EOC) is a complex disease, with multiple histological subtypes recognized. There have been major advances in the understanding of the cellular and molecular biology of this human malignancy, however the survival rate of women with epithelial ovarian cancer has changed little since platinum based-treatment was introduced more than 30 years ago. Since 2006, an increasing number of studies have indicated an essential role for microRNAs in ovarian cancer tumorigenesis. Several microRNA profiling studies have shown that they associate with different aspects of ovarian cancer (tumor subtype, stage, histological grade, prognosis and therapy resistance) and pointed to a critical role for microRNAs in the pathogenesis and progression of EOC. In this review, we discuss the current data concerning the accumulating evidence of the modulated expression of microRNAs in EOC, their role in diagnosis, prognosis and prediction of response to therapy. Given the heterogeneity of this disease, it is likely that increases in long-term survival might be also achieved by translating the recent insights of miRNAs involvement in EOC into novel targeted therapies that will have a major impact on the management of ovarian cancer.